Firm productivity, innovation, and financial development - Sheng Xu; Michael Asiedu; Gabriel Kyeremeh (Cogent Economics & Finance, 2021)
This study utilizes firm-level data from the World Bank's Enterprise Survey Indicator Database, conducted between 2009 and 2018 for 32 countries in Africa, to examine the causal relationship between firm productivity, innovation, and financial development. We show evidence that firm innovation significantly and positively affects firm productivity. We also show the mediating role of well-developed financial markets on productivity. In a well-developed financial market, the impact of firm innovation is significant through the facilitation and financing of innovation activities; and innovative firms to boost productivity and lower production costs. These findings are significant for countries in Africa (and other less-developed countries) who spend less on R&D but can adopt or imitate existing innovative ideas from technology-rich countries for accelerated economic growth and increased productivity.
Keywords: 330; financial development; Firm innovation; new product; new technology; productivity